Understanding color : an introduction for designers - Holtzschue, Linda (Hoboken, NJ : Wiley, 2011)
"Color theory and related color issues are taught in many design schools. The issues surrounding the use of color in a digital realm are of increasing importance. Understanding Color, Fourth Edition offers simple, plain-language explanations of the scientific basis of color perception, an overview of the leading theories of color and explanations of the seeming conflicts among them, and for each concept presented, examples of how theoretical information is applied in solving common problems in color design. This book is invaluable for designers in making sound color choices"--
"Understanding Color, 4e, offers simple, plain-language explanations of the scientific basis of color perception, an overview of the leading theories of color and explanations of the seeming conflicts among them, and for each concept presented, examples of how theoretical information is applied in solving common problems in color design"--
Includes bibliographical references (p. [246]-250) and index.
Keywords: Color in design; DESIGN / Graphic Arts / General